Rapid transient growth at low pH in the cyanobacterium Synechococcus sp. - Kallas, T (1982)
The thermophilic cyanobacterium Synechococcus sp. strain Y-7c-s grows at its maximum rate at a high pH (pH 8 and above) the does not show sustained growth below pH 6.5. However, rapidly growing, exponential-phase cells from high-pH cultures continued to grow rapidly for several hours after transfer to pH 6.0 or 5.0. This transient growth represented increases in mass and protein, but cells failed to complete division. Viability loss commenced well before the cessation of growth, and cells at pH 5.0 showed no net DNA synthesis. When irradiated by visible light, cells at pH 6.0 and 5.0 maintained and internal pH of 6.9 to 7.1 (determined by 31P nuclear magnetic resonance spectroscopy) and an extremely high ATP/(ATP + ADP) ratio even after growth had ceased. Cells exposed to a low pH did not show an increase in the spontaneous mutation rate, as measured by mutation to streptomycin resistance. However, cells already resistant to streptomycin were more resistant to viability loss at a low pH than the parental type. Cultures that could grow transiently at a low pH had higher rates of viability loss than nongrowing cultures in light or darkness. The retention of a high internal pH by cells exposed to a low pH suggested that a low pH acted initially on the cell membrane, possibly on solute transport.